UJI KEKERASAN PADUAN Al-6,7% Cu DENGAN VARIASI TEMPERATUR TUANG DAN TEKANAN HASIL PROSES SQUEEZE CASTING - Rudi Siswanto; Ma’ruf; Galih Aprianto (Scientific Journal of Mechanical Engineering Kinematika, 2021)
Pure aluminum has good castability but mechanical properties not good. Therefore, to improve its mechanical properties, other alloying elements such as magnesium, copper, manganese, silica and some are added. The research was conducted to determine the effect of pouring temperature and pressure on the hardness value of the metal casting material. The casting material uses an aluminum-copper alloy (Al-6.7%Cu). The casting method uses squeeze casting, where the molten metal is allowed to cool in a closed metal mold and is pressurized. The pouring temperature was varied 710°C, 730°C and 750°C. Mixing time for molten metal is 90 seconds with a stirring rotation of 600 Rpm. The metal pressure in the mold was varied from 0 MPa, 2.5 MPa, 5 MPa and 7.5 MPa, with a pressing time of 60 seconds. The temperature of the metal mold used is 250°C. Based on the results of the Brinell scale hardness test (HBN) that the highest hardness value is at a pouring temperature of 710°C with a pressure of 7.5 MPa, the hardness value is 68 HB and the lowest hardness value is at a pouring temperature of 750°C with a pressure of 0 MPa, the hardness value is 34. HB. The results showed that the higher the pouring temperature, the lower the hardness value and the greater the pressure, the higher the hardness value